Minerva oscura : Prolegomeni: la costruzione morale del poema di Dante - Pascoli, Giovanni, 1855-1912 (Salt Lake City, UT : Project Gutenberg, 2013)
"Minerva oscura" by Giovanni Pascoli is a critical examination written in the late 19th century. This work dives into the complexities of Dante Alighieri's Divine Comedy, particularly focusing on the moral construction of the poem and its interpretation. The author appears to explore the deep philosophical and allegorical meanings embedded in Dante's writing, aiming to provide readers with a new perspective on the intricacies of Dante's thought and artistic expression. The opening of "Minerva oscura" presents an introduction where Pascoli expresses his long-standing contemplation regarding Dante's work, referencing previous publications and personal reflections. He describes his initial ambitions for glory in uncovering Dante$1 (Bs mysteries, only to shift towards a more humble aspiration for understanding and appreciation. As he sets the stage for his analysis, he highlights the profound moral and philosophical depths within Dante's Inferno, indicating that the full comprehension of Dante's genius requires diligent exploration of its layers and meanings. Throughout this introductory section, Pascoli underscores the enduring struggle to grasp the essence of Dante$1 (Bs vision, establishing the fundamental themes he will explore in his study. (This is an automatically generated summary.)s
Release date is 2013-04-22
E-text prepared by Carlo Traverso, Claudio Paganelli, Barbara Magni, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by the Google Books Library Project (http://books.google.com)
Keywords: Dante Alighieri, 1265-1321. Divina commedia; Dante Alighieri, 1265-1321 -- Criticism and interpretation